Genetically Encoded Reporter Genes for MicroRNA Imaging in Living Cells and Animals - Yingzhuang Song; Zhijing Xu; Fu Wang (Elsevier, 2020)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression by base paring with the complementary sequences of the target mRNAs, and then exert their function through degrading mRNA or inhibiting protein translation. They play a significant role as a regulatory factor in biological processes of organism development, cell proliferation, differentiation, and cell death. Some of the traditional methods for studying miRNAs, such as northern blot, real-time PCR, or microarray, have been extensively used to investigate the biological properties and expression patterns of miRNAs. However, these methods often require considerable time, cell samples, and the design of effective primers or specific probes. Therefore, in order to gain a deeper understanding of the role of miRNAs in biological processes and accelerate the clinical application of miRNAs in the field of disease treatment, non-invasive, sensitive, and efficient imaging methods are needed to visualize the dynamic expression of miRNAs in living cells and animals. In this study, we reviewed the recent progress in the genetically encoded reporter genes for miRNA imaging.